Hugo Grotius: a lifelong struggle for peace in church and state, 1583-1645 - Nellen, Henk J. M.; Grayson, J. C. (Brill, 2015)
This biography offers a detailed portrait of the famous humanist scholar Hugo Grotius (1583-1645), jurist, politician, Neo-Latin poet and Christian apologist, on the basis of his voluminous correspondence